(3GdSjGSGJ GdYGeI aj GdOhd GdfGejIs - (3Ndjd(B, (3MSjfs ((3HjQhJ(B:s (3OGQ Gdefgd GdHfGJj(B,s, 2007)
(3GdSjGSGJ GdYGeI hEOGQI GdOhdI OQGSI bVGjG hMGdGJ bWGYjI,GdeDSSGJ GdeGdjI hGdGbJUGOjI GdOhdjI GdeDKQI aj SjGSGJ GdOhds
Keywords: (3GdGbJUGOs; (3GdGbJUGO GdOhdjs; (3GdOhd GdfGejIs